Improving Adherence to WHO Surgical Hand Preparation Guidelines in Elective Operating Theatres of a Teaching Hospital in Gujrat, Pakistan: A Completed Audit Cycle - Ali, Zeeshan; Naseem, Umair; Afzal, Saad; Rizwan, Abubakar; Irshad, Madiha; Ashraf, Ahsan (Biological and Clinical Sciences Research Journal, 2025)
Surgical hand preparation is a core infection prevention practice for reducing surgical site infection risk. This audit assessed adherence to World Health Organization (WHO) recommended surgical hand preparation steps and evaluated the effect of a structured improvement package. Methods: A prospective observational audit was conducted in the elective operating rooms of Aziz Bhatti Shaheed Teaching Hospital, Gujrat, Pakistan. A 16-item checklist adapted from WHO guidance covered pre-scrub preparation, hand and forearm washing, rinsing, drying, and final aseptic steps. Compliance was calculated as the percentage of checklist items correctly performed per scrubbing episode. After baseline observation (pre-intervention), corrective measures were implemented (targeted training, visual reminders, and distribution of a standard operating protocol), and a re-audit was performed. Results: A total of 85 surgical hand preparation episodes were observed at baseline and 85 at re-audit across surgery, orthopaedics, and neurosurgery teams. Overall mean compliance improved from 56.9% (SD 11.9) pre-intervention to 89.2% (SD 8.7) post-intervention, an absolute increase of 32.3 percentage points. At baseline, 0% achieved at least 94% compliance (>=15 of 16 items); post-intervention, 47.1% achieved this threshold, and 20.0% completed 100% compliance. Conclusion: Baseline adherence to WHO surgical hand preparation steps was suboptimal. A simple, low-cost quality improvement package was associated with marked improvement across roles and specialties. Ongoing education, supervision, and periodic re-audits are recommended to sustain gains.